The Intercultural Communication Competence of International Students in Indonesia: A Case Study Approach of Darmasiswa Program - Larasati, Ayu; Mayagita, Avradya (Technium Social Sciences Journal, 2021)
Currently, there are many international students come to Indonesia to learn the language and culture. However, it is undeniable that they experienced a very diverse culture shock when they arrived in Indonesia. There are many differences that they experience ranging from weather, food, different ways of eating, time and delay problems to different type of toilet. This study aims to answer the questions on how they adapt to the new culture, and how to become competent in intercultural communication. This is a qualitative research with a case study approach. Data collection was obtained by semi-structured interviews with 8 international students who are studying language and culture in Indonesia. The results showed that intercultural communication competence can be possessed by international student if they have a motivation to learn that can make them more easily to adapt with new cultures and environment.